The Application of ICU Diaries and Its Values in the Care of Critically Ill Patients - Guotao SUN; Xiu JIN; Ning LI; Hui ZHANG; Yunjiao ZHANG; Huaping WEI (Yixue yu zhexue)
This study discussed the role and value of ICU diaries and analyzed their forms and contents. Using content analysis, ICU diaries were systematically reviewed, leading to the identification of 5 themes and 17 sub-themes: patients' treatment progress, expressions of love from family members, the complex emotions experienced by families, patients' reactive emotional changes, and the emotional experiences of medical staffs from their perspective. ICU diaries mainly describe the disease changes of patients, the emotional reactions of patients and their families, the emotions of medical staffs. They document the trajectory of illness progression and critical care experiences during ICU stays, helping patients understand and process their critical illness trauma. These diaries provide psychological support to both patients and their families, significantly alleviating anxiety, depression, and other negative emotions.